PERBANDINGAN HASIL BELAJAR SAINS MELALUI PENILAIAN OTENTIK ANTARA MODEL DISCOVERY DENGAN INQUIRY - Samsuryati Samsuryati; Undang Rosidin; Chandra Ertikanto (Jurnal Pembelajaran Fisika, 2015)
The purpose of this research was to examine the differences in learning outcomes of students knowledge and skills of science between the discovery learning model with the inquiry learning model. The populations in this research were students at SMPN 20 Bandar Lampung. Data of student science learning outcomes were obtained through observation and tests. Based on the test results of data analysis using independent sample t-test, there were the differences in students science knowledge and skills between the discovery learning model with the inquiry learning model. In discovery learning model, students science knowledge was higher than using the inquiry learning model, while students science skills of inquiry learning model was higher than discovery learning model.Penelitian ini bertujuan untuk mengetahui perbedaan hasil belajar pengetahuan dan keterampilan sains siswa antara model pembelajaran discovery dengan inquiry. Populasi dalam penelitian ini adalah siswa SMP Negeri 20 Bandar Lampung. Data hasil belajar sains siswa diperoleh melalui observasi dan tes. Berdasarkan hasil analisis data menggunakan uji independent sample t-tes bahwa terdapat perbedaan pengetahuan dan keterampilan sains siswa antara model pembelajaran discovery dengan inquiry. Pada model pembelajaran discovery pengetahuan sains siswa lebih tinggi dibandingkan menggunakan model pembelajaran inquiry. Sementara pada model pembelajaran inquiry, keterampilan sains siswa lebih tinggi dari pada model pembelajaran discovery.Kata kunci: discovery, hasil belajar, inquiry, keterampilan